The distribution of zakat to Non-Muslims (Muallafah Qulubuhum) in Perlis - Ainul Sofia, Mohd Yusoff (2024)
In Islam, the group of muallaf is eligible to receive zakat. The difference in the definition of muallaf can affect any matter related to the distribution of zakat, whether non-Muslims (muallafah qulubuhum) who have a tendency towards Islam are entitled to receive zakat or not. This paper will analyze the distribution of zakat to non-Muslims (muallafah qulubuhum) in Perlis. Based on interviews with experts from the Mufti Department of Perlis, the Council of Islamic Religion and Malay Customs of Perlis (MAIPs), and Perlis Centre of Wisdom (PCW), this study examines the decisions and views that allow the giving of zakat to non-Muslims under the category of 'muallafah qulubuhum' (those who want to tame their hearts to Islam). Researcher also conducted interviews with muallaf and non-Muslims (muallafah qulubuhum). The 26th Perlis State Fatwa Committee Meeting in 2017 issued the fatwa, which supports this decision with evidence from the Quran and hadith. The research methodology uses a qualitative approach, which combines data collection methods through face-to-face interviews and written responses from key expert informants. Content analysis was done to identify the main themes, such as the purpose of giving zakat, the method of giving zakat, and the implications of zakat to muallaf and non-Muslims (muallafah qulubuhum) in Perlis. The study's findings show that giving zakat to non-Muslims (muallafah qulubuhum) can introduce the beauty and harmony of Islam, as well as educate the Muslim community about the breadth and purity of Islam in a practical context. This finding also confirms that giving zakat to non-Muslims (muallafah qulubuhum) needs to be done carefully, meet certain conditions, and ensure a fair distribution to avoid misunderstandings among the community. Finally, giving zakat to non-Muslims (muallafah qulubuhum) in Perlis not only serves as an effective preaching medium, but it also strengthens social relations and harmony between religions.